ADMINISTRATIVE SERVICES IN A FIELD OF CIVIL AVIATION: TYPES AND PROCEDURES - Husar, Olga A.; Myronets, Oksana M. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: types of administrative services provided in the field of civil aviation, their characteristics and the procedure to provide them are the relevant theme for scientific research according to the new legislation of Ukraine. The State Aviation Administration provides administrative services, such as: cancellation of a license for a right to carry out business activities for the carriage of passengers, dangerous goods and hazardous waste by air on an application; issuance of a license for a right to carry out business activities for the carriage of passengers, dangerous goods and hazardous waste by air; reduction of the conduct of economic activity types for the carriage of passengers, dangerous goods and hazardous waste by air; extension of economic activity types for the carriage of passengers, dangerous goods and hazardous waste by air. Methods: general scientific, philosophical and specially-legal methods of scientific research have been used. Theoretical and legal framework of an institute of administrative services in a field of civil aviation, a procedure for their provision in accordance with the new Licensing conditions for conducting an economic activity for the transportation of passengers, dangerous goods and hazardous waste by air, and changes in a list of administrative services on an example of certification have been researched investigated with the help of general scientific and philosophical methods. A system analysis method has been used for the analysis of modern administrative legislation, scientific works to determine the concepts of «an administrative service» and «administrative service in the field of civil aviation». Results: it is shown that the legislation about administrative services in a field of civil aviation is in the forming stage. It was stressed on conditions to get a license for a right to carry out business activities for the carriage of passengers, dangerous goods and hazardous waste by air according to new Licensing conditions. It was concluded changes in the legislation of Ukraine removed a certification procedure of administrative services that are provided by the State Aviation Service. Discussion: a procedure of administrative services in a field of civil aviation, conditions to get a license a right to carry out business activities for the carriage of passengers, dangerous goods and hazardous waste by air according to the new legislation of Ukraine have been investigated. The development of a concept of «administrative services in a field of civil aviation» and its implementation is an important topic for the future research.